Gaps in the governance of floods, droughts, and heatwaves in the United Kingdom - Carvalho, Priscila; Spataru, Catalina (Frontiers in Earth Science, 2023)
Disaster risk reduction (DRR) and equitable resilience have cross-cutting challenges relevant to the Sustainable Development Goals (SDGs), Sendai Framework (SF) and Climate Change Adaptation (CCA). The capacity of governments to assess, prevent, prepare, respond, and recover from climate related hazards depends on effective laws, planning, policies, governance instruments, equity indicators, harmonized standards, and a holistic approach to cross-sectoral issues and multi-scalar challenges. The principle of subsidiarity guides the UK’s approach to disaster governance, with decisions taken at lowest level and coordinated at different scales (national, sub-national, local). Cross-scale work needed to address large-scale issues and enable the pooling of resources, happens at a sub-national tier created especially for this purpose. At national level, there is a government lead department for each risk identified in the National Risk Assessment, with DEFRA serving as the lead for floods and droughts, while the Department of Health and Social Care is the lead for heatwaves. In this paper we present the current state of the art of the governance of floods, droughts, and heatwaves in the UK, with a focus on pre-emergency phases and the shortage of indicators for assessment of the effectiveness of adaptation for all three disasters, which also compromise the realization and monitoring of targets across all three agendas. The governance of floods counts with the most developed legal framework of the three. Droughts are mainly dealt by the water sector, while heatwaves are treated exclusively as a health issue, leaving gaps with regards to the multiple risks these disasters pose to livelihoods and other sectors. Gaps and challenges that remain are related to siloed institutional approaches, lack of adaptation indicators, lack of sectoral resilience standards, and lack of policy instruments and metrics to promote equitable resilience. Commonly, actions have mainly focused on the response and recovery strategies instead of risk reduction and adaptation to address rising vulnerabilities and exposure.